Understanding the cryotolerance of lactic acid bacteria using combined synchrotron infrared and fluorescence microscopies. Issue 17 (7th September 2015) - Passot, Stéphanie; Gautier, Julie; Jamme, Frédéric; Cenard, Stéphanie; Dumas, Paul; Fonseca, Fernanda
<x xml:space="preserve">Abstract</x> Combining synchrotron-FTIR microspectroscopy and fluorescence microscopy made it possible the simultaneous assessment of biochemistry and physiological state of small bacterial cells for better understanding the mechanisms of cell cryotolerance.